PENGARUH LABEL HALAL, KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK YANG DIKONSUMSI SETIAP HARI - Kornitasari, Yenny; Faidah, Anis Mutifatul (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This research is aimed to explore the effects of halal label, product quality, and price on the decision to purchase daily consumer products by Islamic economics students of universitas brawijaya classes of 2017 to 2019. Variables used in this research are: label halal, product quality, and price as independent variables. Meanwhile the dependent variable in this research is purchase decision. This research used quantitative method, employs multiple linear analysis regression using SPSS 26. Primary data is collected through distributing questionnaires. The sampling technique used was probability sampling in which every member of the population has the same opportunity to become the research sample using the simple random sampling method. Validity and reliability test were done before doing data analysis. After that, the linkert scale data was converted into interval data by using MSI (Method of Successive Interval) before doing multiple linear regression. The regression results show that the halal label, product quality, and price simultaneously affect purchasing decisions. And partially the three independent variables, halal label, product quality and price, have a significant effect on purchasing decisions.